18FDG-PET and Electroencepha- lographic Findings in a Patient Suffering from Musical Hallucinations - Erkwoh, R.; Ebel, H.; Kachel, F.; Reiche, W.; Ringelstein, E. B.; Büll, U.; Saß, H. (Nuklearmedizin - NuclearMedicine, 1993)
The majority of reports on the phenomenon of musical hallucinations suggests that this abnormality is a complication of a progressive peripheral hearing deficit. The present case report and a review of the international literature would, however, indicate that this syndrome may be the result of a dysfunction of the temporal cortex.Fallbericht über das Phänomen der musikalischen Halluzination, nachgewiesen mit PET/18F-FDG. Es wird die (Anti-)Hypothese abgeleitet, daß dieses Syndrom auf einer Funktionsstörung der temporalen Großhirnrinde basiert.
Keywords: Musical hallucination; EEG; PET